Sticky Media. Encoutners with Oil through Imaginary Media Archaeology - Naomie Gramlich (ScholarWorks @ UMass Amherst, 2018)
This paper investigates how media archaeology and the concept of deep time could be taken literally, by bringing authors of early media studies (McLuhan, Innis) together with contemporary eco-material approaches (Gabrys, Parikka) on the topic of oil. Following these conjunctions of media and oil the article first traces certain prevailing narrations in media studies, before turning to the understanding of oil beyond its industrial uses and its catastrophic dimensions in the petro-imaginary of Satin Island by Tom McCarthy. In terms of imaginary media archeology, petro-imaginary provides a conceptual space in which a new relation of images of material reality to media technologies can be drafted, tested, and reviewed. By proposing the figure of sticky media, in contrast to the prevailing metaphors of fluidity, I emphasize their material moments.